Istidrākāt (Rectifications) of Ibn Ḥajar in Fatḥ al-Bārī on Shamsud-Din al-Kermani in Kawakib al-Darārī Regarding judgment of Texts - Rehman Hanif, Matti-Ur-Rehman Bin Abdul; Attaullah (Journal of Islamic and Religious Studies, 2016)
a collection of Aḥādīth of Prophet Muḥammad (May peace and blessing be upon him) compiled by Imām Bukhārī. The Muslim scholars of past and present time gave great importance to this book by making their efforts to extract the treasures hidden in this book and to present the different approaches and benefits of this book. “Al Kawākib al-Durārī” by Imām Al kirmānī is an old explanation of Ṣaḥīḥ Bukhārī. He was among those scholars who were expert in many fields at a time like knowledge about ╓adīth, its narrators, Commentary, Qirā’t, Qur‘ānic Sciences, Islamic Jurisprudence, Arabic language, Faith, Medicine, History, Geography, Astronomy etc. ╓afiz Ibn ╓ajar who also had the specialization in science of hadith and knowledge about biographies of narrators. During studying “Fatḥ al Bārī” I found that ╓afiz Ibn ╓ajar criticized on the commentary of Al kirmānī at many times in relating different sayings and signals. In this article I studied these comments of ╓afiz Ibn ╓ajar on Imam Alkirmani a critical comparison. After research I have found that ╓afiz Ibn ╓ajar has consulted “Al Kawākib al- Durārī” and quoted Imām Al kirmānī’s commentary and added it.This article approves that judgments of ╓afiz Ibn ╓ajar on conversion and transformation of text and on distorted, additional and incomplete words in the text are more authentic than Imām Al kirmānī.